A clinical course of a patient with anorexia nervosa receiving surgery for superior mesenteric artery syndrome - Ken Kurisu; Yukari Yamanaka; Tadahiro Yamazaki; Ryo Yoneda; Makoto Otani; Yoshiyuki Takimoto; Kazuhiro Yoshiuchi (Journal of Eating Disorders, 2021)
Abstract Background Superior mesenteric artery (SMA) syndrome is a well-known but relatively rare complication of anorexia nervosa. Although several reports have proposed surgery for SMA syndrome associated with anorexia nervosa, these have shown poor outcomes or did not reveal the long-term weight course. Thus, the long-term effectiveness of surgery for SMA syndrome in such cases remains unclear. This case report describes a patient with anorexia nervosa who underwent surgery for SMA syndrome. Case presentation An 18-year-old woman presented with anorexia nervosa when she was 16 years old. She also presented with SMA syndrome, which seemed to be caused by weight loss due to the eating disorder. Nutrition therapy initially improved her body weight, but she ceased treatment. She reported that symptoms related to SMA syndrome had led to her weight loss and desired to undergo surgery. Laparoscopic duodenojejunostomy was performed, but her body weight did not improve after the surgery. The patient eventually received conservative nutritional treatment along with psychological approaches, which led to an improvement in her body weight. Conclusions The case implies that surgery for SMA syndrome in patients with anorexia nervosa is ineffective for long-term weight recovery and that conservative treatment can sufficiently improve body weight; this is consistent with the lack of evidence on the topic and reports on potential complications of surgery. Due to difficulties in assessing psychological status, consultation with specialists on eating disorders is necessary for treating patients with severely low body weight.